QUALITY CHARACTERISTICS FERMENTED TILAPIA (Oreochromisniloticus) DIFFERENT CARBOHYDRATE SOURCE - N Ira Sari; Dahlia '; Deby Octavian (Fakultas Perikanan dan Kelautan, Universitas Riau, 2013)
The research was conducted in March 2011 at the laboratory of FishProcessing Technology, Food Chemistry and Food Microbiology, Faculty ofFisheries and Marine Science University of Riau. Aimed of this study was todetermine the characteristics of fermented tilapia with different carbohydratesources. About 5 kg fish weighting 100 gr each was taken from a fish market inPekanbaru. Two groups of fish was fermented repeatedly using roasted rice andfermented bamboo shoot. The fish was fermented at room temperature for 7 days.Quality characteristics of the fermented fish was evaluated for sensory atributes(appearance, flavor, odor, and texture), chemical value ( pH, moisture, NPN,lactic acid), and lactic acid bacteria count. The fish which was fermented withroasted rice was characterized by appearance (attractive, clean, yellowish color),flavor (sour and salty, typical fermentation), odor (acid/alcohol, less fresh, typicalfermentation) and texture (dense, compact, chewy). Chemical value: pH (5,91),moisture (53,6%), NPN (0,12 ml/gr), and lactic acid (1,23 ml/gr), lactic acidbacteria count (5,44 x 10 6 ). Fish fermented with fermented bamboo shoot wascharacterized by appearance (attractive, less clean, opaque), flavor (sour and salty,less savory, not typical fermentation), odor (acids and less alcohol, typicalfermentation) and texture (elastic, compact, chewy). Chemical value: pH (5,38),moisture (59,79%), NPN (0,19 %), and lactic acid (1,71 %), lactic acid bacteriacount (8,167 x 10 6 colony/gr).Keywords: fermented tilapia, roasted rice, and bamboo shoots